High-Sensitivity, Long-Lifetime Flexible Piezoresistive Sensor Based on a Ternary PI/CB/MWCNTs/MXene Conductive Network for Health Monitoring and Speech Recognition - Xuyan Liu; Yitong Gao; Can Yang; Wenqing Bao; Yijie Xia; Qiang Li (ACS Applied Electronic Materials, 2026)
Abstract Flexible piezoresistive sensors hold promising application prospects in wearable health monitoring and human−machine interaction. However, existing devices struggle to achieve a favorable balance among high sensitivity, wide detection range, long cycle life, and low cost simultaneously. In this work, an N/A/CB/MWCNTs/MXene (PCMM) flexible piezoresistive sensor with a ternary conductive network was proposed based on a polyimide (N/A) sponge. The low-cost and high-resilience N/A sponge substrate was prepared via an isocyanate-assisted one-step in situ natural foaming method. A 0D−1D−2D hybrid three-dimensional conductive network was constructed on the substrate using carbon black (CB), multiwalled carbon nanotubes (MWCNTs), and two-dimensional MXene through a vacuum dip-coating process. At a MXene dosage of 30 mg, the composite material achieves a high electrical conductivity of 1.8 × 10−2 S/m with a residual strain of only 6.02%, demonstrating outstanding mechanical resilience. The as-prepared sensor delivers a high sensitivity of 4.393 kPa−1 within the pressure detection range of 0−5 kPa, shows a response time of less than 190 ms, and maintains stable electrical output over 3000 compression cycles. Compared with previously reported N/A-based flexible sensors, this work presents distinct advantages in the structural design of conductive networks and the synergistic optimization of sensitivity and durability. The fabricated sensor has been successfully applied to human motion monitoring, physiological signal detection, and voice recognition, showing great application potential in intelligent health monitoring and next-generation wearable electronics.